SOVEREIGN IMMUNITY DOCTRINE AND SOVEREIGN FUNDS: CHALLENGES AT GLOBAL SCALE - Evgeny V. Popov (Сравнительная политика, 2019)
The article deals with the analysis of difficulties that arise in the current international environment in the context of application of the doctrine of sovereignty to sovereign funds. Based on the review of activities of sovereign funds of such large countries as, e.g., the People’s Republic of China, available investment arbitration rulings, the article focuses on the obstacles preventing the application of traditional doctrine of sovereignty to multi-faceted legal status of sovereign funds and specific features of use of the concepts of absolute and functional immunity when enforcing the court judgments and arbitral awards against the sovereign funds. Following the analysis, the conclusion is drawn that there is currently a serious gap in international law re: sovereign funds’ treatment and there is a need to outline the key prospective directions on how this gap can be overcome.